Exploring Factors behind Patient Nonadherence to Intravitreal Anti-Vascular Endothelial Growth Factor Injections in Macular Diseases - Efrat Naaman; Noa Yanir-Prat; Diana Shair-Nakhleh; Nitai Bar; Beata Miller; Anna Fishman; Shiri Zayit-Soudry (Ophthalmic Research)
Introduction: In recent years, intravitreal injections (IVTs) of vascular endothelial growth factor (VEGF) inhibitors have become the standard of care for several macular disorders. Frequently, the therapeutic course requires numerous injections, posing a burden on patients. Nonadherence to treatment may result in reduced visual outcomes, therefore understanding and addressing the underlying causes is imperative. Methods: A cross-sectional study of patients who missed their scheduled appointment for anti-VEGF IVT as part of the routine management of their macular disease at a single tertiary center between November 2020 and February 2021. A telephone survey was conducted and patient medical charts were reviewed for ophthalmological data. Results: A total of 100/556 (18%) patients who failed to attend their scheduled anti-VEGF IVT appointments were documented. Among these subjects, the average age was 66 (SD ± 14) years with a nearly equal gender distribution of 49:51 F:M ratio. Reported no-show reasons included concurrent illness (39%), administrative issues such as missing financial coverage forms or scheduling problems (28%), and lack of motivation (11%). Additionally, 73% of patients who missed appointments expressed a need for accompaniment, and 74% resided outside the hospital city. Conclusions: Study results highlight modifiable factors contributing to no-shows to anti-VEGF IVT, such as poor transportation access, complicated administrative processes, and difficulty rescheduling missed appointments. Understanding potential obstacles to anti-VEGF IVT therapy, particularly those that are preventable, can enhance adherence and potentially improve the clinical outcome.